Research Trend of Publications Concerning Antibody-Drug Conjugate in Solid Cancer: A Bibliometric Study - Qi, Xiangjun; Li, Yanlong; Liu, Wei; Wang, Yifan; Chen, Zhuangzhong; Lin, Lizhu (Frontiers in Pharmacology, 2022)
Background: Antibody-drug conjugate (ADC) is a promising therapy for solid cancer that has raised global concern. Although several papers have reviewed the current state of ADCs in different solid cancers, a quantitative analysis of the publications in this field is scarce. Methods: Publications related to ADC in the field of solid cancer were obtained from the Web of Science Core Collection. Data analyses were performed with VOSviewer 1.6.9, HistCite 2.1, CiteSpace V and R package Bibliometrix. Results: A total of 3482 records were obtained in the holistic field and 1197 in the clinical field. A steady growth in the number of publications was observed. The USA was the leading contributor in this field. Krop IE was the most influential author. The most productive institution was Genentech Inc, while Mem Sloan Kettering Canc Ctr was the most cited one. The most impactful journal was the Journal of Clinical Oncology. A total of 37 burst references and 5 burst references were identified between 2017-2022 in the holistic and clinical field, respectively. Keywords analysis indicated that ADCs research mainly involved breast cancer, triple-negative breast cancer, ovarian cancer, small cell lung cancer, prostate cancer, gastric cancer, and urothelial carcinoma. ADC agents including trastuzumab emtansine, trastuzumab deruxtecan, sacituzumab govitecan, enfortumab vedotin and rovalpituzumab tesirine were highly studied. Targets including HER-2, trophoblast cell-surface antigen, delta-like ligand 3 and nectin-4 were the major concerns. Conclusion: This study analyzed publications concerning ADCs in the field of solid cancer with bibliometric analysis. Further clinical trials of ADCs and designs of the next-generation of ADCs are the current focuses of the field. Acquired resistance of ADCs and biomarkers for ADC therapy efficacy monitoring are future concerns.